Evolution of Television Cyberjournalism: Artificial Intelligence Avatars as 'News Anchors' in International Media - Flores-Vivar, Jesús Miguel; Moreno-Espinosa, Pastora; Barros-Garbín, Serafín (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The evolution of artificial intelligence has caused a disruption in people's lives, affecting their personal and professional experiences. In the field of journalism and the media, especially television, a turning point has been reached, so more in-depth analysis is needed to establish a diagnosis of the impact that AI systems are having on models that some see as the new news presenters in online news companies. This study focuses on analysing and reflecting on the role and impact that news presenters are having on television (even in non-media institutions but related to journalism and communication), based on generative artificial intelligence models in Ibero-American, European and Asian media.